Electroactive nano short fiber for osteoarthritis cartilage repair and preparation method thereof
By preparing electroactive nanofibers, using their conductivity and lubricating properties, the problem of difficulty in reducing joint friction and achieving cartilage regeneration in the prior art is solved, and the effect of significantly improving chondrocyte function and promoting cartilage repair under ultrasound stimulation is achieved.
Patent Information
- Application Number
- CN202510021536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to simultaneously reduce friction between joints and achieve cartilage regeneration or reverse the pathological process of osteoarthritis through physical means.
Electroactive nanofiber films are prepared by electrospinning technology, and heat treatment and modified graphene oxide treatment are carried out. Finally, reaction is carried out in a mixture of alkaline dopamine and phosphatidylcholine to form electroactive nanofibers with conductive and lubricating properties.
Under ultrasound stimulation with 1W, 650KHz and 50% duty cycle, the Sirt1 expression in OA chondrocytes was significantly upregulated, mitochondrial respiratory chain function was improved, mitochondrial damage was slowed, ATP production capacity was increased, inflammatory factors were inhibited and the degradation of extracellular matrix was degraded, and cartilage repair was promoted.
Smart Images

Figure CN119770719A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an electrically active nano short fiber for repairing osteoarthritis cartilage and a preparation method thereof. Background Art
[0002] The vicious cycle between joint lubrication disorders and mitochondrial damage is the core pathological basis for the progression of osteoarthritis (OA). How to cut off the vicious cycle of mitochondrial damage while restoring joint lubrication function is the key to reversing OA and promoting cartilage repair.
[0003] In the early stages of OA, the impairment of cartilage lubrication function exacerbates the friction and wear between cartilages, interferes with the normal function of the mitochondrial respiratory chain, promotes the release of reactive oxygen species, and then triggers an inflammatory cascade including NOD-like receptor pyridinyl domain 3 (NLRP3) and caspase-1, leading to chondrocyte pyroptosis while regulating the behavior of chondrocytes, prompting chondrocytes to release aggrecanase, phosphohydrolase, matrix metalloproteinase (MMP), and disintegrin and metalloproteinase with thrombospondin motifs, accelerating the degradation of the extracellular matrix. The extracellular matrix is a key factor affecting the rheological and frictional properties of articular cartilage. After the destruction of the extracellular matrix, the lubrication properties of the cartilage are lost again, and the high friction state between the cartilages further damages the mitochondrial energy metabolism homeostasis, thus forming a vicious cycle between lubrication disorders and mitochondrial damage. Therefore, restoring the joint lubrication function while cutting off the vicious cycle of mitochondrial damage is the key to reversing OA and promoting cartilage repair.
[0004] At present, the main treatment strategy for the vicious cycle of OA is to develop exogenous lubricants. Although existing exogenous lubricants can effectively reduce friction between joints, they cannot achieve cartilage regeneration or reverse the pathological process of OA. The root cause of this limitation is the lack of sufficient attention to the mitochondrial damage caused by long-term exposure of damaged chondrocytes to high friction and wear.
[0005] The high friction state of OA articular cartilage exacerbates the damage of mitochondria in chondrocytes and disrupts the dynamic balance of extracellular matrix synthesis and degradation by inducing inflammatory cascade reactions, ultimately leading to the degeneration of articular cartilage. Although the combined use of chitosan and lecithin can slow down mitochondrial damage and improve joint degeneration, the side effects of oral medication limit its long-term application.
[0006] Regarding avoiding oral medication and using only physical methods to treat OA, although there are sporadic studies in the prior art that have achieved the effect of promoting the release of inflammatory factors and increasing ATP production, the results obtained are relatively limited, and it is difficult to achieve cartilage regeneration or reverse the pathological process of OA. Summary of the invention
[0007] In view of the defects of the prior art, the purpose of the present invention is to provide a biomedical material that can not only effectively reduce friction between joints by physical means, but also achieve cartilage regeneration or reverse the pathological process of OA. Specifically, it is to provide electroactive nano-short fibers for osteoarthritis cartilage repair with the aforementioned functions.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing electroactive short nanofibers for repairing osteoarthritis cartilage, the method comprising the following steps:
[0010] (1) A composite material of gelatin (Gel, the same below), polylactic acid (PLA, the same below) and glycine crystals is electrospun to prepare a nanofiber membrane (NF, the same below), and the obtained nanofiber membrane is prepared into short fibers; the short fibers are then heated to obtain a short fiber scaffold (NF-Sponge, the same below);
[0011] (2) breaking the product obtained in step (1) into pieces (denoted as NS-pieces, the same below) and reacting with graphene oxide (abbreviated as GO, the same below) to obtain modified graphene oxide short fibers (denoted as NS-GO, the same below);
[0012] (3) The modified graphene oxide obtained in step (2) is immersed in a mixed solution of alkaline dopamine (abbreviated as DA, the same below) and phosphatidylcholine (abbreviated as PMPC, the same below) to react, thereby obtaining the electroactive nano short fibers (denoted as NS-rG@PMPC, the same below).
[0013] When preparing the electroactive short nanofibers of the present invention, due to the hydrophilicity of the gelatin substrate, the short nanofibers will quickly decompose when in contact with water. The inventors heat-treat the freeze-dried short nanofiber scaffolds by thermal crosslinking to obtain short fiber scaffolds with stability. As shown in the embodiments of the present invention, the short fiber scaffolds after heat treatment can significantly reduce the number of free amino and carboxyl groups in gelatin, and the CN tensile vibration band strength is significantly enhanced.
[0014] The present invention uses a mixed solution of alkaline dopamine and phosphatidylcholine to treat modified graphene oxide short fibers, and alkaline dopamine self-polymerizes on the modified graphene oxide short fibers to form polydopamine, and the graphene oxide is in situ reduced to reduced graphene oxide (abbreviated as rG, the same below) through an amidation reaction. At the same time, the catecholamine groups on the polydopamine and the alcohol and amine groups in the phosphatidylcholine are grafted onto the short fibers in one step through a Schiff base or Michael addition reaction. This modification process not only gives the short fiber bulk electrical conductivity, forms an electrical signal network, and ensures the electrical activity of the short fiber, but also forms a solid hydration layer on the surface of the short fiber due to the strong water absorption capacity of the phosphatidylcholine, giving the short fiber lubrication properties.
[0015] Preferably, in step (1), when the obtained nanofiber membrane is prepared into short fibers, the nanofiber membrane is first cut into small pieces, and then uniformly dispersed in a tert-butanol solution by high-speed centrifugation in a homogenizer, and then the uniformly dispersed short fibers are shaped and freeze-dried for 24 hours.
[0016] Preferably, in step (1), when the short fibers are subjected to heat treatment, the short fibers are heated at 180° C. for 2 hours.
[0017] Preferably, in step (1), when preparing the nanofiber membrane, the specific method is: using microsol electrospinning technology, mixed electrospinning is carried out in an atmosphere with a relative humidity of 30±10%, and the solution flow rate through a flat-head 21-gauge needle is 2 ml / hour; the distance from the needle tip to the collecting drum is maintained at 15 cm; the applied electric field is set to 15 kV; the polarized solution is sprayed on a grounded aluminum drum and wrapped with aluminum foil, and rotated at a speed of 400 rpm to collect the nano short fiber membrane.
[0018] Preferably, in step (2), when the product obtained in step (1) is reacted with graphene oxide, the specific method is: immersing the short fibers in step (1) in a graphene solution for 24 hours to modify the graphene on the short fibers; the concentration of the graphene solution is 4 mg / mL.
[0019] Preferably, in step (3), the weight ratio of alkaline dopamine to phosphatidylcholine is 1:1-8.
[0020] The present invention also provides electrically active nano short fibers for repairing osteoarthritis cartilage prepared by the above preparation method.
[0021] The present invention also provides the use of the above-mentioned electroactive nano short fibers in preparing materials for promoting OA cartilage repair. More specifically, it provides the use of materials for promoting OA cartilage repair by cutting off the vicious cycle of mitochondrial damage while restoring joint lubrication function.
[0022] The electroactive nano short fibers provided by the present invention have a low friction coefficient, and significantly up-regulated the expression of Sirt1 in OA chondrocytes under ultrasonic stimulation of 1W, 650KHz, and 50% duty cycle, and slowed down the degree of mitochondrial damage under oxidative stress by improving the function of the mitochondrial respiratory chain, increasing the ATP production capacity to 23.074±1.87pmol / min, and inhibiting the release of inflammatory factors and the degradation of the extracellular matrix, while also providing a guarantee for the renewal of the hydrated lubricating layer. The electroactive nano short fibers provided by the present invention have great potential in promoting OA cartilage repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 and Figure 2 This is a diagram showing the results of the verification and characterization experiments of the lubricating electroactive short fibers obtained in the embodiments of the present invention;
[0024] Figure 3 This is a graph showing the experimental results of the lubricating performance of the lubricating electroactive short fibers obtained in an embodiment of the present invention;
[0025] Figure 4 This is a graph showing the electrical properties experimental results of the lubricated electroactive short fibers obtained in an embodiment of the present invention;
[0026] Figure 5-7 This is a graph showing the experimental results of the cytotoxicity and proliferation-promoting ability of the lubricating electroactive short fibers obtained in the examples of the present invention;
[0027] Figure 8-10 This is a diagram showing the experimental results of the protective effect of lubricated electroactive short fibers on mitochondrial function obtained in an embodiment of the present invention;
[0028] Fig.11 This is a graph showing the experimental results of the protective ability of the lubricating electroactive short fibers obtained in an embodiment of the present invention on chondrocytes;
[0029] Figure 12-13 This is a diagram showing the results of an in vivo validation experiment of using the lubricating electroactive short fibers obtained in an embodiment of the present invention for OA cartilage repair treatment;
[0030] Fig.14 This is a graph showing the results of an RT-PCR experiment performed in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel in this field based on the above invention content still fall within the scope of protection of the present invention.
[0032] Example 1
[0033] 1. Experimental materials and equipment:
[0034] Gelatin (Sigma, USA, Catalog No.: 73865), polylactic acid (Aladdin, China, Catalog No.: P169115), graphene (Xfnan, China), glycine (Sigma, USA), dopamine (Aladdin, China, Catalog No.: A303863), phosphatidylcholine (Aladdin, China), Tris-HCl (Aladdin, China), tert-butyl alcohol (Macklin, China), hexafluoroisopropanol (Macklin, China), ATDC5 mouse chondrocytes (IMMO, China), CCK-8 (Beyotime), LDH kit (Beyotime), TRIzol reagent (Invitrogen, USA) , Sirt1 (abways, China), PGC1-a (Proteintech, China), NLPR3 (Proteintech, China), Caspase-1p10 (Bioss, China), Aggrecan (Proteintech, China), Col2α1 (Proteintech, China), MMP13 (Proteintech, China), ADAMTS (Proteintech, China), protease and phosphatase inhibitors (Sigma–Aldrich), RIPA lysis buffer (Beyotime), PVDF membrane (Millipore, USA), QuickBlock TM blocking buffer (Beyotime), (Proteintech, China), ECL enhanced chemiluminescence kit (Beyotime, China), Seahorse XF cell mitochondrial stress test kit (AgilentTechnologies, USA), cell culture plate (Agilent Technologies, USA), IL-1B (Sigma, USA), DCFH-DA (Beyotime, China), MitosoxRed (5uM) (Thermo Fisher Scientific, China), JC-1 membrane potential detection kit (Beyotime, China);
[0035] Homogenizer (IKA-T25DIGITAL S025), freeze dryer (SCIENTZ-10N / A), scanning electron microscope (Hitachi SU5000), Fourier transform infrared spectrometer (Thermo Fisher Scientific Nicolet iS20), Raman spectrometer (Horiba LabRAM HR Evolution), X-ray photoelectron spectrometer (Thermo Scientific-Alpha), contact angle meter (Kunshan Shengding SDC 350KS), friction and wear tester (Bruker-CETR UMT-2), four-probe contact instrument (ST27428), confocal microscopy (Leica, Japan), ABI7500 sequencing detection system (Applied Biosystems, Foster City, USA), SYBR Premix Ex Tag Kit (TaKaRa, Dalian, China), Seahorse XF analyzer (XFe24, Agilent Technologies, USA), transmission electron microscope (JEM-1400FLASH, Japan), micro-computed tomography (micro-CT) imaging system (SkyScan1172, BrukerBioSpin, Belgium).
[0036] 2. Experimental Methods
[0037] 1. Preparation of lubricated electroactive short fibers
[0038] 0.96g of gelatin (Gel) and 0.24g of polylactic acid (PLA) were dissolved in hexafluoroisopropanol at a mass ratio of 4:1 to prepare 10ml of a Gel / PLA mixed solution with a concentration of 12wt%. Subsequently, the pre-prepared β-glycine was added to the mixed solution to a final concentration of 50mg / ml, and it was ensured to be uniformly dispersed by continuous stirring for 2 hours. The mixed electrospinning operation was carried out in an atmosphere with a relative humidity of 30±10%, using a flat-headed No. 21 needle to control the flow rate of the solution to 2ml / h. At the same time, the distance from the needle tip to the collection drum (grounded aluminum drum, covered with aluminum foil) was kept at 15cm. An electric field of 15kV was applied to drive the spinning process. The spinning solution was sprayed on the aluminum drum at a speed of 400r / min, and finally the nanofiber short fiber membrane was collected for vacuum drying to remove the residual trace solvent. Next, the nanofiber membrane was cut and the shredded spinning membrane was evenly dispersed in the tert-butyl alcohol solution. The homogenization was carried out at 13000r / min for 30 minutes using a homogenizer (IKA-T25DIGITAL S025), followed by freeze drying for 48 hours using a freeze dryer (SCIENTZ-10N / A) to obtain an uncrosslinked scaffold (NF-Sponge). In order to enhance the stability of the scaffold structure, it was placed in an oven and subjected to a thermal crosslinking treatment at 180°C for 2 hours to obtain (NS-Sponge). Afterwards, the NS-Sponge was further broken up, and the obtained NS-pieces were immersed in a graphene (GO) solution (4mg / ml) for 24 hours and rinsed with deionized water to remove free GO. Then the obtained NS-GO short fibers were placed in a mixture of dopamine (2 mg / ml, DA) trihydrochloride buffer (10 mM, PH = 8.5) and phosphatidylcholine (PMPC) (1:1, 1:4, 1:8) and soaked at 37 ° C for 24 h to reduce graphene oxide to rGO and graft PMPC onto the NS-rG short fibers in one step. Finally, the injectable ultrasonically responsive lubricated electroactive short fibers (NS-rG@PMPC) were obtained by washing with deionized water.
[0039] 2. Characterization of lubricated electroactive short fibers:
[0040] After the electrospun fiber membrane was cut to a suitable size, the material was first macroscopically observed using a digital camera. A small amount of platinum was then sprayed and its microscopic morphology was detected using a scanning electron microscope (Hitachi S U5000). The chemical composition of the material was analyzed by Fourier infrared spectrometer (Thermo Fisher Scientific Nicolet iS20) to detect the number of amino and carboxyl groups in the lubricating electroactive short fibers, Raman spectrometer (Horiba LabRAM HR Evolution) to detect the characteristic G peak and D peak of graphene in the composite material, and X-ray photoelectron spectrometer (Thermo Scientific-Alpha) was used to determine the composition of elements in the composite material. The hydrophilicity of the material was detected by a contact angle meter (Kunshan Shengding SDC 350KS), and the lubrication performance was evaluated by a friction and wear tester (Bruker-CETR UMT-2). In the experiment, the lubricating electroactive fiber membrane was flatly pasted on a glass slide as the lower component, and the articular cartilage of DMM rats (euthanized) was used as the upper component. Lubrication tests were performed under different loads (0.8N, 1N, 1.2N, 1.4N) and rotation speeds (4mm / min, 8mm / min, 12mm / min, 16mm / min, 20mm / min). In order to evaluate the hydration lubrication effect of electrospun Gel / PLA nanofiber membranes after one-step PMPC grafting, Gel / PLA and different grafting ratios (1:1, 1:4, 1:8) membrane samples were selected to evaluate the changes in COF under different experimental conditions (whether in a water environment). After the lubrication test was completed, the samples were allowed to dry naturally and photos were taken to observe the actual wear. The conductivity of the material was evaluated by a four-probe contact instrument (ST27428). The lubricated electroactive short fibers were placed in a 50mL centrifuge tube containing 20mL high DMEM medium and shaken at 37°C for 1, 5, 10, 15 and 20, 25, 30 days. The material was then rinsed and its conductivity was measured. In addition, in order to explore the ultrasonic transduction characteristics of lubricated electroactive short fibers, the composite materials were treated with focused ultrasound (650 KHz, 50% duty cycle) of different intensities (0.5 W, 1 W, and 2 W), and the electrical output performance of the samples was detected by an oscilloscope and a potentiostat.
[0041] 3. Cell culture:
[0042] ATDC5 mouse chondrocyte progenitor cells were placed in DMEM medium (Gibco, China) containing 10% fetal bovine serum and 1% dual antibiotics (penicillin and streptomycin) and cultured in an incubator at 37°C and 5% CO2. The culture medium was changed every 48h. After the chondrocyte density reached about 80%, it was digested with trypsin, separated, and subcultured. When the chondrocytes reached the 3rd to 5th generation and reached sufficient cell density, the experiment was started.
[0043] 4. Cytotoxicity and cell proliferation assays
[0044] The effects of lubricated electroactive short fibers on the proliferation and toxicity of ATDC5 chondrocytes were detected by AO / EB staining test, CCK-8 assay and LDH toxicity test, respectively. Lubricated electroactive short fibers were co-cultured with chondrocytes in a confocal dish, and the culture medium was removed after 1 and 3 days. The chondrocytes after intervention were then washed with PBS, and composite dye (containing calcein-AM and propidium iodide) was added, cultured for 15 minutes, and observed under a confocal fiber microscope (Leica, Japan). CCK-8 (Beyotime) and LDH kits (Beyotime) were used to evaluate cell proliferation and cytotoxicity in 96-well plates after 24 hours of co-culture.
[0045] 5. Synthesis of related genes detected by RTqPCR
[0046] To evaluate the effect of ultrasound-mediated electroactive short fibers on chondrocytes, RT-PCR was used to measure the expression of Sirt1 and genes related to ECM metabolism (ADAMTS, MMP13, Col-2α1, Aggrecan). Specifically, total RNA from chondrocytes was extracted using TRIzol reagent (Invitrogen, USA), and the purity and concentration of the RNA solution were obtained by measuring the relative absorbance at 280 nm and 260 nm. The corresponding cDNA was synthesized by 1 μg RNA and Revert-Aid FirstStrand cDNA Synthesis Kit (TaKaRa, Dalian, China). The amplification process of cDNA mediated in RT-PCR was completed using ABI7500 Sequencing Detection System (Applied Biosystems, Foster City, USA) and SYBR Premix Ex Tag Kit (TaKaRa, Dalian, China).
[0047] 6. Western blotting to detect the expression of related proteins
[0048] In order to verify whether ultrasound-mediated electroactive short fibers can effectively upregulate the expression of Sirt1 protein in chondrocytes and the protective effect of upregulating Sirt1 on chondrocytes, Western blot experiments were performed to evaluate the expression levels of Sirt1 (abways, China) and downstream target protein PGC1-a (Proteintech, China), as well as proteins related to chondrocyte protection and inflammation, NLPR3 (Proteintech, China), Caspase-1p10 (Bioss, China), Aggrecan (Proteintech, China), Col2α1 (Proteintech, China), MMP13 (Proteintech, China), and ADAMTS (Proteintech, China). (i) Chondrocytes were collected and added to RIPA lysis buffer (Beyotime) containing protease and phosphatase inhibitors (Sigma–Aldrich); (ii) the solution was centrifuged at 12,000 rpm for 30 min at 4°C to separate the supernatant; (iii) proteins were separated by SDS-PAGE, transferred to a 0.45 μm PVDF membrane (Millipore, USA), blocked with QuickBlock™ blocking buffer (Beyotime), and then incubated with primary antibodies at 4°C overnight. The proteins were then incubated with secondary antibodies (Proteintech, China) at room temperature for 1 h; (iv) protein expression was detected using an ECL enhanced chemiluminescence kit (Beyotime, China), and quantitatively analyzed using ImageJ.
[0049] 7. Measurement of mitochondrial respiratory chain activity
[0050] To further verify the effect of ultrasound-mediated electroactive short fibers on the mitochondrial respiratory chain in chondrocytes, the activity of the mitochondrial respiratory chain was assessed using the Seahorse XF Cell Mitochondrial Stress Test Kit (Agilent Technologies, USA). The specific steps are as follows: (i) After treatment according to the experimental design, ATDC5 cells (1×10 5 (ii) IL-1B (Sigma, USA) was added to induce cellular oxidative stress model, and each group was intervened after 12 hours; (iii) 24 hours later, oligomycin (1 μM), carbonyl cyanide trifluoromethoxyphenylhydrazone (1 μM), antimycin A (0.5 μM) and rotenone 0.5 μM were added to the culture plate according to the requirements of the kit; (iv) The oxygen consumption of each group of cells was measured using Seahorse XF analyzer (XFe24, Agilent Technologies, USA).
[0051] 8. Research on ROS, mitochondrial membrane potential and mitochondrial morphology
[0052] ATDC5 chondrocytes were seeded in 6-well plates, and IL-1B (5 nM) was added to the culture medium to establish an oxidative stress model. Each experimental group was subjected to different intervention treatments and cultured for 24 h. (i) Reactive oxygen species (ROS) were detected by treating each group of cells with DCFH-DA (10 μM) (Beyotime, China) and MitosoxRed (5 uM) (Thermo Fisher Scientific, China) dyes for 20 minutes, washing three times, and then observing with a confocal microscope (Leica, Japan); (ii) Mitochondrial membrane potential was measured by staining the cells with JC-1 membrane potential detection kit (Beyotime, China) for 30 minutes and then observing under the same microscope; (iii) Mitochondrial morphology was observed by scraping the cells with a cell scraper, centrifuging at 3000 rpm for 5 minutes, and discarding the supernatant. Glutaraldehyde fixative precooled at 4°C was slowly added; after dehydration, the samples were embedded in Epon-812 pure embedding medium, and then sliced in a LEICAUC7rt ultramicrotome to obtain 60–90 nm slices; the slices were first treated with uranyl acetate and lead citrate for 5–10 min and air-dried, and finally observed under a transmission electron microscope (JEM-1400FLASH, Japan).
[0053] 9. Immunofluorescence staining
[0054] ATDC5 cells were seeded in confocal dishes (biosharp, China). After 24 h of intervention, the culture medium was removed and the cells were fixed with 4% paraformaldehyde (biosharp, China) for 30 min. (i) The samples were treated with 0.3% Triton X-100 (Biofroxx, Germany) for 10 min and blocked with 5% goat serum (Beyotime, China) for 1 h; (ii) The cells in each experimental group were incubated with primary antibodies rabbit anti-Sirt1 (abways, China), rabbit anti-Caspase-1p10 (Bioss, China), rabbit anti-Col2α1 (Proteintech, China), rabbit anti-Matrix Metalloproteinase 13 (Proteintech, China), mouse anti-PGC1-a (Proteintech, China), and mouse anti-NLRP3 (Proteintech, China) at 4°C overnight, and then the corresponding fluorescent secondary antibodies were applied and incubated at 37°C for 1 h; (iii) The cytoskeleton was stained with FITC-labeled phalloidin (Servicebio, China) for 1 h, and then the cell nucleus was stained with DAPI (Servicebio, China); (iv) Finally, the cells were observed under a confocal microscope and quantified using ImageJ software.
[0055] 10. Cell pyroptosis staining
[0056] AO / EB (Yuanye, China) fluorescence staining experiment was used to observe the state of cell membrane to reflect the protective effect of ultrasound-mediated lubricated electroactive short fibers on cartilage. (i) ATDC5 cells were seeded in a confocal dish (biosharp, China). After 24 hours of intervention, the culture medium was removed and the cells were washed three times with PBS; (ii) AO / EB working solution was prepared: appropriate amounts of reagent (A), reagent (B), and reagent (C) were taken and diluted to prepare AO / EB working solution according to the ratio of reagent (A): reagent (B): reagent (C) = 1:1:8; (iii) 50ul of working solution was added to each experimental group and incubated at room temperature for 30 minutes; (iv) Finally, the cells were observed under a confocal microscope and quantified using ImageJ software.
[0057] 11. Animal Models
[0058] The animal experiment was approved by the Animal Ethics Committee of the First Affiliated Hospital of Chongqing Medical University (ethical approval number: IACUC-CQMU-202407019). 8-week-old male Sprague-Dawley rats were used to construct the OA disease model. The specific steps are as follows: (i) Intraperitoneal injection of sodium pentobarbital solution (3 mg / 100 g) for general anesthesia; (ii) Removal of fur around the knee joint. Using a sterile scalpel, an incision was made on the skin of the rat's knee joint, the patellar ligament was moved to one side, and the medial patellar ligament was destroyed from bottom to top using an ophthalmic scalpel; subsequently, the patellar ligament was repositioned and sutured, and two weeks after the modeling was completed, the rats were grouped according to the experimental design; (iii) The experimental group was injected with the corresponding short fiber biomaterial once every 2 weeks, the sham group was injected with the same amount of PBS solution, and the ultrasound group was treated with ultrasound (HIFU, China) intervention once every two days for 5 minutes each time two weeks after surgery. The ultrasound parameters were: 1 MHz, 250 mW / cm2, 50% duty cycle.
[0059] 12. X-ray, Micro CT and histological staining evaluation
[0060] Six weeks after DMM surgery, the rats were euthanized and their knee joints were removed intact and fixed in 4% paraformaldehyde for three days. (i) X-rays were taken using an X-ray imager (Faxitron X-ray, USA) with the selected parameters (32 kV, 6 mAs) to observe the changes in the width of the knee joint space. Subsequently, the bone specimens of each experimental group were subjected to arthrography using a high-resolution micro-computed tomography (micro-CT) imaging system (SkyScan 1172, Bruker BioSpin, Belgium); the relative osteophyte volume and subchondral bone density were evaluated based on the micro-CT scanning and reconstruction results; (ii) the tissues were decalcified and softened by immersion in a 10% ethylenediaminetetraacetic acid (EDTA) solution for three weeks, and the decalcification solution was changed every two days; (iii) the decalcified samples were dehydrated in ethanol, embedded in paraffin, and then sectioned with 5 μm thickness; (iv) immunofluorescence staining with safranin O-fast green, H&E, and Col2α1 was performed, and the degree of cartilage damage was quantitatively evaluated according to the modified Mankin's scoring system. The Mankin's score is scored in different levels based on the overall structure, cell structure, safranin staining, and tide line integrity, with the highest score being 14 points and the lowest score being 0 points. 0-1 is normal cartilage; 2-6 is early OA; 7-10 is mid-stage OA; 11-14 is late OA. (v) Finally, the fluorescence quantitative analysis of Col2α1 protein was performed using Image J software.
[0061] 13. Statistical analysis
[0062] Graphpad Prism 9 (GraphPad Software, USA) was used for statistical analysis. Independent sample t-test was used to evaluate statistical differences between the two groups, and one-way analysis of variance (ANOVA) was used for multiple data groups. All experiments were designed to include at least three parallel repeated samples. Statistical significance was set at P < 0.05, marked as *P < 0.05, **P < 0.01, ***P < 0.001. P > 0.05 indicates that there is no statistically significant difference between the two groups (ns).
[0063] 3. Experimental Results
[0064] 1. Verification and characterization of lubricated electroactive short fibers
[0065] After modification with GO and PDA, the white NS-Sponge changed from white to brown and finally to black, indicating that rGO was successfully modified on the NS-Sponge scaffold. Figure 1 As shown in part c. Scanning electron microscopy (SEM) images at different magnifications reveal the structure of all short fibers, which are composed of randomly arranged fibers, very similar to the natural extracellular matrix (ECM). The surfaces of NF, NF-Sponge, NS-Sponge and NS-pieces all exhibit uniform and smooth characteristics, while the fiber surfaces of NS-rG and NS-rG@PMPC show obvious roughness and granularity, which preliminarily indicates the successful attachment of reduced graphene oxide (rG) and phosphatidylcholine (PMPC). It is worth noting that despite the deposition of rG and PMPC, the bionic ECM mesh fiber structure of the fiber scaffold was not destroyed (see Figure 1 Raman spectroscopy analysis confirmed the successful modification of rG, with its characteristic vibration peak D peak (1352cm -1 ) and G peak (1590cm -1 ) is clearly visible in the spectrum, such as Figure 1 As shown in part E. In order to verify the successful grafting of phosphatidylcholine as a lubricating molecule, the inventors conducted Fourier transform infrared spectroscopy (FTIR) analysis on NS-rG samples treated with different proportions of dopamine (DA) and PMPC. The analysis results are shown in Figure 1 As shown in the F part, at 1400-1600cm -1 The characteristic absorption peaks of benzene ring were observed in the range of 1060 cm -1 and 1244cm -1 The typical absorption peaks of PO and P=O were detected at 100 nm and 100 nm, respectively. These findings provide strong evidence for the successful grafting of GO and PMPC on the fiber scaffold. In addition, the qualitative and quantitative analysis of X-ray photoelectron spectroscopy (XPS) also confirmed the successful grafting of GO and PMPC on the NS scaffold. Specifically, Figure 1 As shown in the GH section, after the scaffold was modified by GO, the percentage of carbon and oxygen atoms increased, and with the increase of PMPC content, the proportion of nitrogen and phosphorus atoms also increased accordingly. Since phosphorus only comes from PMPC, this further confirms the successful grafting of PMPC on NS-rG, as shown in Figure 1 The qualitative analysis is shown in the IK section. Figure 2 .
[0066] 2. Lubricating properties of electroactive short fibers
[0067] The lubrication performance of NS-rG@PMPC short fibers is a prerequisite for promoting cartilage repair. Therefore, the inventors conducted detailed measurements of the lubrication performance of NS-rG@PMPC through friction and wear tests and contact angle tests.
[0068] 2.1 Friction and wear test
[0069] like Figure 3 As shown in part a, in order to evaluate the lubricating effect of nanofibers grafted with PMPC, the inventors adopted an experimental method to simulate the contact friction between cartilage and different nanofiber membranes: the femur of osteoarthritis OA rats was taken, the distal end of the femur was fixed, and the proximal end was rubbed against the nanofiber membranes of NS-rG, NS-rG@PMPC (1:1), NS-rG@PMPC (1:4), and NS-rG@PMPC (1:8) at different pressure combinations and friction speeds, and the friction coefficient was measured.
[0070] The friction coefficient (COF) of PLA / Gel / β-Gly nanofiber membrane is relatively high, about 0.72. However, after grafting with PMPC, the COF decreases significantly, and the COF of the membranes with a ratio of 1:1, 1:4, and 1:8 drops to about 0.65, 0.41, and 0.23, respectively. This indicates that with the increase of the PMPC grafting amount, the friction coefficient of the nanofiber membrane gradually decreases, showing a more excellent lubrication performance, such as Figure 3 In addition, wear time, load and rotation speed are also important factors affecting COF. Figure 3 As shown in part c, the COF of the four nanofiber membranes increased rapidly within 10 seconds, especially the NS-rG nanofiber membrane, which had the most significant COF increase due to the lack of lubrication factor. The nanofiber membrane grafted with PMPC at a ratio of 1:8 reached a stable state the fastest, and its COF was only half of that of the NS-rG nanofiber membrane. This result shows that in the presence of water molecules, the surface of the fiber membrane grafted with PMPC can induce the formation of a stable hydration layer, thereby effectively reducing friction and improving lubrication performance. The increase in load will also affect the COF, such as Figure 3As shown in part d, when the load increases from 0.8N to 1.2N, the COF of all nanofiber membranes increases. This may be because the increase in load leads to an increase in elastic deformation, thereby increasing the friction. Nevertheless, the COF of the nanofiber membrane grafted with PMPC is always lower than that of the pure NS-rG nanofiber membrane. In addition, the increase in rotation speed will reduce the contact time, thereby reducing the elastic deformation and friction, as shown in Figure 5. Figure 3 The wear image after the friction test is shown in part e. Figure 3 As shown in part f, the wear of the Gel / PLA / β-Gly nanofiber membrane in both air and water is relatively serious, indicating that water alone has no significant lubricating effect on the Gel / PLAβ-Gly membrane. However, as the proportion of grafted lubricating molecules increases, the inventors found that only obvious wrinkles were observed on the 1:8 nanofiber membrane, and there was no damage to the nanofiber membrane, and the structure was almost intact in water. This is because compared with the air environment, the aqueous solution allows more water molecules around the zwitterionic charge of the phosphorylcholine group, helping it to form a more stable hydration layer. Due to the presence of residual charges on H and O atoms, the water molecule is actually a larger electric dipole, so the water dipole is attached to it through the interaction between the different charges of the zwitterionic material. These water molecules can withstand greater pressure and respond in a fluid-like manner under shear, thereby greatly reducing the COF at the interface (i.e., enhancing lubrication).
[0071] 2.2 Contact angle experiment
[0072] In order to further verify the lubrication performance of electroactive short fibers, the inventors also measured the water contact angle. The study showed that the smaller the water contact angle, the better the lubrication performance of the material and the thicker the hydrated lubrication layer formed. Figure 3 As shown in the middle g part, the water contact angles of Gel / Pla / β-Gly, 1:1, 1:4, and 1:8 nanofibers are 59.60°, 55.28°, 47.15°, and 30°, respectively. The water contact angles of all samples are less than 90°, indicating that the nanofibers have a superhydrophilic surface, and as the PMPC content increases, the water contact angle decreases, further indicating that these nanofiber membranes can better retain water and promote compatibility with surrounding tissues, thereby effectively repairing the hydrated lubricating layer of cartilage.
[0073] In summary, it can be concluded that due to the presence of hydration lubrication, PMPC-grafted nanofibers have better wear resistance than pure Gel / PLA / β-Gly nanofibers, and the higher the PMPC grafting ratio, the better the lubrication performance of the composite material. Therefore, in order to make the lubricating electroactive short fibers better exert their lubrication performance, the inventors used the composite electrospinning material grafted with PMPC at a ratio of 1:8 in subsequent experiments.
[0074] 3. Electrical properties of lubricated electroactive short fibers
[0075] The electrical properties of NS-rG@PMPC nanofibers are the material basis for promoting cartilage repair. Stable electrical activity is a prerequisite for the later activation of Sirt1 to maintain mitochondrial homeostasis in chondrocytes. Therefore, the inventors tested the electrical properties of electroactive short fibers from two aspects: conductivity and piezoelectric properties.
[0076] 3.1 Conductive properties of lubricated electroactive short fibers
[0077] like Figure 3 As shown in the middle part, when the NS-rG and NS-rG@PMPC integrated circuits are integrated compared with pure NS, the LED bulb can be seen to be significantly brighter. The conductivity of the three was detected and it was found that the conductivity of NS-rG and NS-rG@PMPC nanofibers was significantly increased compared with the almost undetectable conductivity of pure NS. Although the conductivity of NS-rG@PMPC may be lower than that of NS-rG due to the deposition of PMPC, it is also much higher than the conductivity of the NS group, which is sufficient to promote the repair of articular cartilage. Although conductive biomaterials have great application potential in the medical field, their conductivity stability in vivo remains a challenge because complex biological environments, such as biofluids and acid-base conditions, may interfere with conductivity and cause negative effects such as unstable electrical properties, liquid leakage, and potential biocompatibility issues. Considering that stable conductivity is required to transmit long-term electrical signals required by cells or tissues, the inventors incubated the short fiber solution (1 mg / mL) in an oscillator at 37°C for up to 30 days and measured the conductivity stability of the short fibers within a predetermined number of days, such as Figure 3 The conductivity measurements showed no significant changes, indicating that these matrices can maintain their conductivity for at least 30 days. In addition, the NS-rG@PMPC nanofibers exhibited high conductivity in the wet state ( Figure 3 k part), which means that NS-rG@PMPC nanofibers can transmit bioelectric signals in response to endogenous electric field (EF) and remain stable in synovial fluid.
[0078] 3.2 Piezoelectric properties of lubricated electroactive short fibers
[0079] Ultrasonic responsiveness of nanofibers Figure 3As shown in the middle part, due to the presence of β-Gly crystals, NS-rG@PMPC nanofibers show sensitive acoustic-electric response under different intensities of sound pressure, and the output voltage increases with the increase of ultrasonic intensity. The inventors used a voltage oscilloscope to detect the output voltage of the lubricated electroactive short fibers under the action of continuous ultrasound of different intensities (0.5W, 1W and 2W), which were about 1V, 1.31V and 1.81V respectively. They also used pulsed ultrasound of different intensities to stimulate the lubricated electroactive short fibers and found that when the ultrasonic stimulation stopped, the voltage output immediately stopped. This phenomenon shows the sensitive response ability of the electroactive short fibers to ultrasonic stimulation, as shown in Figure 1. Figure 3 As shown in the middle part. Also considering the key role of stable piezoelectric properties in tissue repair, the inventors took the electrospinning solution with a specific incubation time in an oscillator at 37°C and detected its output voltage under 1W ultrasonic intensity. Although the output voltage of the composite electrospinning material fluctuated within the 10th to 20th day, it rebounded in the next 10 days and eventually stabilized. This phenomenon may be related to the dissolution and precipitation process of glycine in the solution, as shown in Figure 3 In addition, like the conductive properties, the piezoelectric properties of the electroactive short fibers also show an increasing trend in the wet state, as shown in the q part of the figure. Figure 3 The good conductivity and sensitive acoustic-electrical responsiveness of NS-rG and NS-rG@PMPC short fibers are attributed to the stable and uniform distribution of glycine and rG on the scaffold and the effective reduction of PDA, which provides a prerequisite for activating Sirt1 through late electrical stimulation and stabilizing the mitochondrial respiratory chain.
[0080] 4. Study on the cytotoxicity and proliferation-promoting ability of lubricated electroactive short fibers
[0081] 4.1 Biocompatibility of lubricated electroactive short fibers
[0082] Biocompatibility is the prerequisite for the function of lubricating electroactive short fibers. Therefore, the inventors conducted cytotoxicity and cell proliferation experiments. First, the biosafety of the composite electrospun materials was tested by live-dead staining experiments. The experimental groups were control group, ultrasound group (US), NS, NS-rG@PMPC and US@NS-rG@PMPC. Live-dead staining was performed on chondrocytes co-cultured with lubricating electroactive short fibers for 1 day and 3 days. Figure 4 As shown in parts a, f, and g, in all groups, the number of cells increased with the increase of culture time, which preliminarily indicated that the electroactive short fibers had no cytotoxicity. Secondly, the absorbance of chondrocytes co-cultured with the composite electrospun materials for 3 days was detected by CCK-8 and LDH experiments. There was no significant difference between the groups, which further confirmed that the lubricated electroactive short fibers were low-toxic materials that met the biosafety standards. Figure 4 As shown in parts h and i.
[0083] 4.2 Determination of ultrasound parameters
[0084] To determine the optimal ultrasound parameters to produce an optimal current that upregulates Sirt1 and promotes mitochondrial stabilization in lubricated electroactive short fibers in response to ultrasound stimulation. Figure 4 As shown in part b, the inventors divided the chondrocytes into five groups: a control group, a Blank group, a first experimental group, which was stimulated with 0.5W, 650KHZ, and 50% duty cycle ultrasound for 15 minutes, called 0.5W-US, a second experimental group, which was stimulated with 1W, 650KHZ, and 50% duty cycle ultrasound for 15 minutes, called 1W-US, and a third experimental group, which was stimulated with 2W, 650KHZ, and 50% duty cycle ultrasound for 15 minutes, called 2W-US. Sirt1 is a key gene for maintaining mitochondrial stability. The expression of Sirt1 mRNA was detected by polymerase chain reaction (PCR). Figure 4 As shown in part c, there was no statistically significant difference in the expression of Sirt1 mRNA between the 0.5W-US group and the Blank group, indicating that the ultrasound intensity of 0.5W cannot effectively maintain the stability of mitochondria. On the contrary, compared with the Blank group, the expression of Sirt1 mRNA in the 1W-US group and the 2W-US group increased significantly, but the Sirt1 mRNA in the 2W-US group showed a downward trend compared with the 1W-US group. Therefore, the inventors preliminarily determined 1W, 650KHZ, and 50% duty cycle as effective parameters for promoting mitochondrial stability in chondrocytes.
[0085] 4.3 Ability of lubricating electroactive short fibers to promote chondrocyte proliferation and migration
[0086] Chondrocytes participate in the whole process of cartilage repair, and their proliferation and migration ability affect the repair of cartilage. In order to further determine the potential therapeutic effect of 1W-US ultrasound intensity on cartilage repair, the inventors evaluated the ability of lubricated electroactive short fibers to promote chondrocyte proliferation through cell scratch and migration experiments. Figure 4 As shown in part e, Transwell and scratch experiments showed that 1W-US ultrasound stimulation significantly affected the proliferation and migration of chondrocytes.
[0087] In summary, the lubricated electroactive short fibers not only have good biocompatibility, but also sensitively respond to 1W, 650KHZ, and 50% duty cycle ultrasonic stimulation to upregulate the expression level of Sirt1 in chondrocytes and improve the proliferation and migration ability of chondrocytes.
[0088] 5. Protective effect of lubricated electroactive short fibers on mitochondrial function
[0089] Sirt1 is a core gene that regulates mitochondrial oxidative respiratory function and plays an important role in the mitochondrial quality control system. Its activation in OA chondrocytes has been shown to rescue mitochondrial damage. The present invention focuses on the core mechanism of the mitochondrial respiratory chain, and further explores the effect of Sirt1's increased expression on the stability of the mitochondrial respiratory chain in response to ultrasound-mediated lubricated electroactive short fiber stimulation through Western Blot experiments, immunofluorescence experiments, oxygen consumption rate (OCR) experiments, mitochondrial electron microscopy, and mitochondrial oxidative stress status, thereby revealing its protective effect on mitochondrial function.
[0090] 5.1 Western Blot and Immunofluorescence Detection of Sirt1 and Downstream Factor PGC1-α
[0091] Through Western Blot and immunofluorescence experiments, the inventors detected the expression of Sirt1 and its downstream protein peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α). Figure 5 Part A, Figure 7 As shown in the middle L part, the electroactive short fibers significantly activated the expression of Sirt1 and PGC-1α in OA chondrocytes through ultrasound stimulation. Since SIRT1 targeting PGC1-α can upregulate nuclear respiratory factors 1 and 2 (Nrf1 / 2) to restore mitochondrial oxidative respiration capacity, the inventors preliminarily speculated that lubricated electroactive short fibers have the potential to maintain the stability of the mitochondrial respiratory chain.
[0092] 5.2 Detection of mitochondrial respiratory chain activity by oxygen consumption (OCR)
[0093] In order to detect the activity of mitochondrial respiratory chain, the inventors measured the oxygen consumption of chondrocytes within 80 minutes, such as Figure 5 As shown in part B. The first 20 minutes represent the basal respiratory capacity of mitochondria in each group of chondrocytes, 20-40 minutes represent the ability of mitochondria to synthesize ATP under basal respiratory capacity, 40-60 minutes represent the maximum respiratory capacity of mitochondria in response to exogenous inflammatory stimulation, and 60-80 minutes represent the potential of mitochondria to synthesize ATP. Subsequently, the basal respiratory capacity, ATP production capacity, maximum respiratory capacity, and spare respiratory capacity of mitochondria were quantified. The results are shown in Figure 5 Part C, Figure 6The DF part in the figure shows that the basal mitochondrial respiratory capacity and ATP production of chondrocytes in the OA group were significantly lower than those of normal cells in the control group, indicating that the mitochondrial respiratory chain of chondrocytes in the OA group was severely damaged in the inflammatory environment. At the same time, the maximum respiratory capacity and ATP production potential (indicators of improved mitochondrial respiratory chain activity) of the OA group were also significantly lower than those of the control group, indicating that chondrocytes encountered challenges in promoting cartilage repair under pathological conditions. After ultrasound stimulation, the four indicators of mitochondrial respiratory chain activity in the electroactive short fiber group were significantly higher than those in the OA group. Among them, the ATP production capacity increased from the original 20.192±2.46pmol / min to 23.074±1.87pmol / min, indicating that the ultrasound-responsive electroactive short fibers effectively activated the mitochondrial respiratory chain in OA chondrocytes, providing ATP support for cell proliferation and cartilage repair.
[0094] 5.3 Mitochondrial electron microscopy
[0095] Sirt1 also provides important protection for mitochondrial oxidative respiration capacity by upregulating mitochondrial fusion proteins 1 and 2 (MFN1 / 2) and optical atrophy-associated factor 1 (OPA1) through targeting PGC1-α to mediate mitochondrial fusion and fission. Therefore, observation of mitochondrial morphology by transmission electron microscopy can further confirm the protective effect of ultrasound-mediated lubricated electroactive short fibers on mitochondria. Figure 7 As shown in the middle H part, it can be observed that the OA group has swollen mitochondria and broken inner membrane cristae, indicating that the mitochondria are severely damaged. After treatment with NS-rG@PMPC, the mitochondrial damage is slightly alleviated, but there are still some mitochondrial swelling, indicating that the repair of the endogenous electric field can also restore mitochondrial damage to a certain extent. However, in the group treated with US@NS-rg@PMPC, there is almost no mitochondrial swelling, the mitochondrial structure is clear, and the inner membrane cristae are intact.
[0096] 5.4 Improvement of Antioxidative Stress Capacity
[0097] Impaired mitochondrial respiratory chain function is often accompanied by leakage of the electron transport chain (ETC), which leads to increased production of oxygen free radicals (ROS), which in turn damages mitochondrial DNA (mtDNA), forming a vicious cycle and eventually developing into OA. The inventors found that lubricated electroactive short fibers not only restored the stability of the mitochondrial respiratory chain by upregulating Sirt1, but also significantly enhanced its ability to resist oxidative stress. Using ROS fluorescent probes dichlorofluorescein diacetate (DCFH-DA) and MitosoxRed detection, it was observed that the ultrasound-mediated lubricated electroactive short fiber group showed the strongest antioxidant capacity ( Figure 5 The mitochondrial membrane potential was further analyzed by JC-1 staining, and the results showed that the mitochondrial membrane potential of the US@NS-rG@PMPC group was close to that of the normal control group, indicating that it has a significant protective effect on the mitochondrial membrane ( Figure 7 (Part K)
[0098] In conclusion, the elevated expression of Sirt1 in OA chondrocytes in response to ultrasound-mediated lubricated electroactive short fiber stimulation can enhance the protective effect on mitochondrial function by maintaining the stability of the mitochondrial respiratory chain.
[0099] 6. The protective ability of lubricating electroactive short fibers on chondrocytes
[0100] Excessive accumulation of reactive oxygen species (ROS) caused by mitochondrial dysfunction has been shown to be the most significant activating factor of the inflammasome NLRP3. Activated NLRP3 regulates multiple downstream factors including Caspase-1p10, triggering a series of inflammatory cascade reactions, leading to the release of inflammatory factors interleukin-1B (IL-1B) and interleukin-18 (IL-18), ultimately promoting chondrocyte pyroptosis and aggravating the pathological process of OA. In the present invention, the inventors innovatively adopted a co-culture system of chondrocytes and lubricating electroactive short fibers, and introduced exogenous ultrasonic stimulation, and evaluated the potential protective effect of the composite electrospinning material on chondrocytes through immunofluorescence staining and Western Blot experiments.
[0101] 6.1 Pyroptosis
[0102] like Figure 8 As shown in parts A and B, through acridine orange / ethidium bromide (AO / EB) fluorescence staining experiments, the inventors observed that the chondrocyte membrane in the ultrasound-mediated lubricated electroactive short fiber group remained intact, and its state was close to that of the untreated control group (Control), preliminarily revealing that electrical stimulation enhanced the anti-oxidative stress capacity of chondrocytes by upregulating Sirt1, inhibited cell pyroptosis, and thus achieved cell protection.
[0103] 6.2 Western Blot and Immunofluorescence Detection of Proteins Related to ECM Dynamic Balance
[0104] In the process of OA, the release of inflammatory factors and the imbalance of ECM homeostasis are the key factors leading to cartilage degradation. Therefore, the protective effect of lubricating electroactive short fibers on chondrocytes can be further verified by detecting inflammatory factors IL-18, tumor necrosis factor-a (TNF-a) and related proteins involved in the ECM decomposition process. Figure 8 As shown in the CD part, compared with the Blank group, ultrasound-mediated lubricated electroactive short fibers significantly inhibited the release of the above inflammatory factors, demonstrating its potential anti-inflammatory effect. Further Western Blot analysis ( Fig. 9) revealed that after 24h of IL-1B intervention, the pro-degradation proteins such as NLRP3, Caspase-1p10, ADAMTS and MMP13 in the Blank group were significantly upregulated compared with the control group, while the expression of protective proteoglycan (Aggrecan) and II collagen (Col2α1) was significantly downregulated. It is worth noting that there was no significant difference in protein expression levels between the ultrasound group, NS group and NS-rG@PMPC group compared with the Blank group. However, in the early stage of IL-1B stimulation (6h, 12h), exogenous ultrasound-activated lubricated electroactive short fibers significantly inhibited the expression of NLRP3, Caspase-1p10, ADAMTs and MMP13 proteins in chondrocytes, while promoting the synthesis of Aggrecan and Col2α1. Aggrecan and Col2α1 are the main components of ECM and are essential for maintaining cartilage structure. The upregulation of MMP13 and ADAMTS accelerates the degradation of cartilage. In addition, the results of RT-PCR experiments ( Fig.14 ) is consistent with the Western Blot results and also proves that ultrasound-mediated lubricated electroactive short fibers have the ability to maintain the homeostasis of ECM decomposition metabolism. In order to intuitively show the protective effect of ultrasound-mediated lubricated electroactive short fibers on cartilage, the inventors conducted immunofluorescence staining experiments for NLRP3, Caspase-1p10, Col2α1 and MMP13 ( Figure 8-9 ), the results showed that after IL-1β treatment, Col2α1 was significantly reduced in the Blank group, while the expression of NLRP3, Caspase-1p10, and MMP13 was significantly enhanced; on the contrary, these changes were significantly reversed in the lubricated electroactive short fiber group stimulated by ultrasound.
[0105] In summary, ultrasound-mediated lubricated electroactive short fibers increase the protective effect on chondrocytes by intervening in the inflammatory cascade mediated by ROS / NLRP3 / Caspase-1p10, inhibiting cell pyroptosis, and maintaining the catabolic balance of ECM.
[0106] 7. In vivo validation of lubricated electroactive short fibers for OA cartilage repair
[0107] Further in vivo validation also confirmed the significant therapeutic effect of US@NS-rG@pMPC on OA cartilage repair. The present invention successfully established a rat OA model by transecting the anterior cruciate ligament. The experimental rats were randomly divided into six groups: sham operation (Sham) group, PBS group, simple ultrasound (US) group, short fiber (NS) group, lubricated electroactive short fiber (NS-rG@PMPC) group, and ultrasound combined with lubricated electroactive short fiber (US@NS-rG@PMPC) group. Two weeks after the OA model was established, each treatment group was injected with the corresponding material. The injection frequency was once every two weeks. At the same time, for the group receiving ultrasound treatment, the inventor set it once every two days, 5 minutes each time, with an intensity of 1MHZ and a power of 250mW / cm 2 After 4 weeks of intervention, the inventors euthanized the rats and collected the rat knee joints for X-ray imaging, micro-CT reconstruction, tissue staining, and immunofluorescence staining ( Figure 11-13 ).
[0108] The characteristics of progressive osteoarthritis include narrowing of the joint space (JSW), osteophyte formation, and sclerosis of the subchondral bone. The inventors used X-ray scanning and Micro CT imaging techniques to analyze the changes in the width of the knee joint space and osteophyte formation in rats after four weeks of treatment. Fig.11 As shown in part b. X-ray results showed that compared with the Sham group, the cartilage gaps in the knee joints of rats in the PBS group, US group, NS group, and NS-rG@PMPC group were significantly narrowed, among which the JSW of the PBS group was only 0.5 times that of the Sham group, while there was no significant difference in JSW between US@NS-rG@PMPC and Sham. Micro CT reconstruction further verified the X-ray results and clearly showed the pathological changes in the knee joints of rats in each group. Quantitative analysis showed that although the volume and mass of osteophytes increased in all experimental groups, the increase in the US@NS-rG@PMPC group was much lower than that in the other groups ( Fig.11 It is particularly noteworthy that compared with the Sham group, the US@NS-rG@PMPC group had no significant difference in subchondral bone mineral density, with a value of 1.005±0.005 times, while the value of the PBS group was 1.45±0.02 times (p<0.05), showing the potential advantage of the US@NS-rG@PMPC treatment group in cartilage protection.
[0109] In addition to imaging examinations, hematoxylin-eosin (H&E) and safranin fast green staining were used to compare and analyze the histological changes of the cartilage surface in different treatment groups. Fig.12As shown in parts A and B, compared with the Sham group, the cartilage surface of the PBS group showed obvious irregular morphology and erosive cracks, which indicates that the inventors have successfully established a rat OA experimental model. Further analysis found that in the US group, NS group and NS-rG@PMPC group, the cartilage surface showed varying degrees of degeneration. However, in the ultrasound combined with lubricated electroactive short fiber treatment group, the degree of cartilage degeneration was significantly alleviated. In order to quantitatively evaluate the degree of cartilage damage, the inventors used a modified Mankin scoring system for quantitative analysis. The relevant scoring criteria are shown in Table 1. Although the cartilage damage score in all treatment groups increased compared with the Sham group, the cartilage score of US@NS-rG@pMPC was significantly lower than that of the PBS group. In order to more intuitively demonstrate the therapeutic effect of ultrasound combined with lubricated electroactive short fibers in cartilage repair, the inventors conducted gross observations of the distal femur of each group, as shown in the figure. Fig.12 As shown in the middle C part, compared with the Sham group, the distal femurs of the PBS group, US group, NS group and NS-rG@pMPC group showed obvious cartilage destruction and wear. In contrast, the cartilage surface of the US@NS-rG@pMPC treatment group was smooth and the degree of wear was less. In order to study the effect of ultrasound combined with lubricated electroactive short fibers on the repair function of chondrocytes, the inventors used immunofluorescence staining to quantitatively analyze the expression of COL2 and MMP13. The results showed that during the progression of OA, the COL2 synthesized by chondrocytes in the PBS group was significantly lower than that in the Sham group, while MMP13 was higher than that in the Sham group. After NS-rG@pMPC treatment, the expression of COL2 and MMP13 showed an opposite trend, indicating that NS-rG@pMPC restored the physiological function of cartilage to a certain extent through endogenous electric field repair. Compared with other experimental groups, US@NS-rG@pMPC significantly increased the expression of COL2 and decreased the expression level of MMP13, indicating that US@NS-rG@pMPC more effectively promoted the recovery of the physiological function of chondrocytes and promoted cartilage repair in OA by enhancing electrical signals and repairing endogenous electric fields.
[0110] Table 1
[0111]
[0112]
[0113] In summary, the ultrasound-mediated lubricated electroactive short fibers of the present invention maintain the catabolic balance of cartilage by virtue of the dual mechanisms of hydration lubrication and ultrasonic piezoelectric transduction, thereby achieving a protective effect on cartilage.
Claims
1. A method for preparing electroactive short nanofibers for osteoarthritis cartilage repair, characterized in that: The preparation method comprises the following steps: (1) preparing a nanofiber membrane by electrospinning a composite material of gelatin, polylactic acid and glycine crystals, and preparing the obtained nanofiber membrane into short fibers; freeze-drying the short fibers and then heating them to obtain a short fiber scaffold; (2) crushing the product obtained in step (1) and reacting it with graphene oxide to obtain modified graphene oxide short fibers; (3) Immersing the modified graphene oxide obtained in step (2) in a mixed solution of alkaline dopamine and phosphatidylcholine for reaction, thereby obtaining the electroactive nanofibers.
2. The method for preparing electroactive short nanofibers for osteoarthritis cartilage repair according to claim 1, characterized in that: In step (1), when preparing the obtained nanofiber membrane into short fibers, the nanofiber membrane is first cut into small pieces, and then evenly dispersed in a tert-butyl alcohol solution by high-speed centrifugation in a homogenizer, and then the evenly dispersed short fibers are shaped and freeze-dried for 24 hours.
3. The method for preparing electroactive short nanofibers for osteoarthritis cartilage repair according to claim 1, characterized in that: In step (1), when the short fibers are subjected to heat treatment, the short fibers are heated at 180° C. for 2 hours.
4. The method for preparing electroactive short nanofibers for osteoarthritis cartilage repair according to claim 1, characterized in that: In step (1), when preparing the nanofiber membrane, the specific method is: using microsol electrospinning technology, mixed electrospinning is carried out in an atmosphere with a relative humidity of 30±10%, and the solution flow rate through a flat-head 21-gauge needle is 2 ml / hour; the distance from the needle tip to the collection drum is maintained at 15 cm; the applied electric field is set to 15 kV; the polarized solution is sprayed on a grounded aluminum drum and wrapped with aluminum foil, and rotated at a speed of 400 rpm to collect the nano short fiber membrane.
5. The method for preparing electroactive short nanofibers for osteoarthritis cartilage repair according to claim 1, characterized in that: In step (2), when the product obtained in step (1) is reacted with graphene oxide, the specific method is: immersing the short fibers in step (1) in a graphene solution for 24 hours to modify the graphene on the short fibers; the concentration of the graphene solution is 4 mg / mL.
6. The method for preparing electroactive short nanofibers for osteoarthritis cartilage repair according to claim 1, characterized in that: In step (3), the weight ratio of alkaline dopamine to phosphatidylcholine is 1:1-8.
7. The method for preparing an electroactive short nanofiber for repairing osteoarthritis cartilage according to claim 1 or 6, characterized in that: In step (3), the reaction conditions of the reaction are: soaking at 37° C. for 24 hours.
8. An electroactive short nanofiber for osteoarthritis cartilage repair, characterized in that: The electroactive short nanofibers are prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the electroactive short nanofibers according to claim 8 in the preparation of materials for promoting OA cartilage repair.
10. The use according to claim 9, characterized in that: The application is to prepare materials that can restore joint lubrication function while cutting off the vicious cycle of mitochondrial damage to promote OA cartilage repair.
Citation Information
Cited By
Injectable ultrasonic response piezoelectric and conductive integrated short fiber as well as preparation method and application thereof
CN120797397A
Application of OPA1 in preparation of product for treating and / or preventing traumatic osteoarthritis
CN121775118A